Dynamic chromatin organization in the cell. Issue 1 (9th April 2019) - Prieto, Eloise I.; Maeshima, Kazuhiro
Abstract : The organization and regulation of genomic DNA as nuclear chromatin is necessary for proper DNA function inside living eukaryotic cells. While this has been extensively explored, no true consensus is currently reached regarding the exact mechanism of chromatin organization. The traditional view has assumed that the DNA is packaged into a hierarchy of structures inside the nucleus based on the regular 30-nm chromatin fiber. This is currently being challenged by the fluid-like model of the chromatin which views the chromatin as a dynamic structure based on the irregular 10-nm fiber. In this review, we focus on the recent progress in chromatin structure elucidation highlighting the paradigm shift in chromatin folding mechanism from the classical textbook perspective of the regularly folded chromatin to the more dynamic fluid-like perspective.